2015
DOI: 10.1016/j.ssci.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Personality, risk cognitions and motivation related to demand of risk mitigation in transport among Norwegians

Abstract: There is insufficient knowledge regarding the role of personality traits, transport-related risk cognitions and safety motivation for demand for transport risk mitigation. The aim of this study is to test a model aimed to predict public demand for transport risk mitigation by these psychological risk constructs. A mailed self-completion questionnaire survey was conducted in a random sample of the Norwegian population aged 18-65 years obtained from the Norwegian population registry (n = 1947). Results from stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Additionally, this research found that individual attributes and personality traits should be considered when risk is communicated (Nordfjaern & Rundmo, 2015). Sensation seeking is negatively correlated with age.…”
Section: Managerial Implicationsmentioning
confidence: 75%
“…Additionally, this research found that individual attributes and personality traits should be considered when risk is communicated (Nordfjaern & Rundmo, 2015). Sensation seeking is negatively correlated with age.…”
Section: Managerial Implicationsmentioning
confidence: 75%
“…For instance, personality traits in the Big Five Questionnaire have comprised extraversion, neuroticism, agreeableness, openness to experience, and conscientiousness; the NEO Personality Inventory measures excitement-seeking, anxiety, and aggression. In addition, many scales of personality traits have combined and developed from the abovementioned scales [6,16,[37][38][39][40].…”
Section: Formulation Of the Teoretical Modelmentioning
confidence: 99%
“…Te research analyzed personality traits (PT) through fve subfactors that comprised a total of 24 items. Tese subfactors were anxiety (AN, four items), anger (AG, fve items), sensation-seeking (SS, fve items), altruism (AL, six items), and normlessness (NL, four items), which were sourced from materials such as [6,16,38,40]. Participants were assigned a rating on a fve-point Likert-type scale, with responses ranging from "strongly disagree (1)" to "strongly agree (5)."…”
Section: Data Collectionmentioning
confidence: 99%
“…In a survey of offshore oil operators, Rundmo found a positive correlation between risk perception and risk behavior in a survey of offshore oil operators, but risk perception could not predict risk behavior [40]. Then, together with Nordfjaern, the relationship between risk perception and traffic risk was discussed [41]. In the purple clustering led by the University of Queensland, the institutional research is mainly on roads and medicine.…”
Section: Institutional Distribution Of Literaturementioning
confidence: 99%